Consumo da telefonia móvel por jovens universitários: o papel da comunicação na construção da identidade do jovem - Arrais, Denio Dias (2011)
The relations that involve communication and consumption with culture impact what is currently known by contemporary society. These relations influence people in their way of communicating and consuming. Through this paper we seek to understand the processes of communication and the building of the identity of the young university student, being understood here as an actor for modern consumption. The theoretical basis for this research lies in working out the concepts of communication and consumption, culture and identity. We analyzed the movements of communication and consumption from the use by the young university student of mobile telephony and cell phones. Consumption and citizenship are dealt with using the concepts of Garcia Canclini, who sees consumption as one of the dimensions of the communication process and social belonging. In Featherstone we notice reflections over the culture and consumption in the late modern times, context in which the young people make their presence. In order to write about technology and convergence culture present in practices and ways of communication of the young people, we used the ideas of Jenkins. Hall provides understanding of the building of the identity of the young university student as a complex and cultural process characterized by the ways of using, consuming and communicating, typical of mobile telephony. The adopted methodology for this paper uses, besides the bibliographic research, a quantitative mapping with the goal of obtaining data on the cultural consumption of the young university student. The tools used for this mapping were structured questionnaires, which were run in colleges of the capital and countryside areas of the state of São Paulo. The mapping was useful to obtain elements dealt with in the interviews that were carried out to identify the attribution of meaning given by young people to consumption of cell phones, taking into consideration the theoretical reflections discussed in the bibliographic research. It was possible, then, to identify the presence of cell phones in the common relations of the young people and we have identified the processes of the building of identity. In the general aspect of this paper, we had as a result the fact that the young people have in their cell phones a tool that goes beyond the material and functional usage. The cell phone is a person s telephone. In it we can find parts of the identity of its users in the personalization of content.